Characterization of finite simple semigroup digraphs - Meksawang, J.; Panma, S.; Knauer, U. (Algebra and Discrete Mathematics, 2011)
This paper characterizes directed graphs which are Cayley graphs of finite simple semigroups, i.e. of a subspecies of completely regular semigroups. Moreover we investigate the structure of Cayley graphs of finite simple semigroups with a one-element connection set. We introduce the conditions for which they are isomorphic and connected.